A three-phase epidemiological study of short and long sleepers in a middle-aged Chinese population: prevalence and characteristics - Hao,Y.L. (2014)
Epidemiological studies of short and long sleepers have not been conducted previously. We collected socioeconomic, psychological, and polysomnographic characteristics of 6501 parents (3252 men and 3249 women) of 4036 primary school children in Guangzhou city. The study data were collected in three phases. The overall prevalence of short (5 h or less) and long (10 h or more) sleep duration was 0.52 and 0.64%, respectively. Long sleepers had higher Eysenck Personality Questionnaire neuroticism scores [odds ratio (OR)=1.224, 95% confidence interval (CI)=1.047-1.409] and lower education levels (OR=0.740, 95%CI=0.631-0.849) than short sleepers. In the polysomnographic assessment, short, long, and normal sleepers (7-8 h) shared similar durations of Stage 3 sleep (short=25.7±10.7, long=20.3±7.9, and normal=28.0±12.8 min, F=1.402, P=0.181). In daytime multiple sleep latency tests, short sleepers (10/19, 52.6%) were more prone to have a short sleep latency (≤8 min) than long sleepers (2/23, 8.7%). In addition to different sleep durations, neuroticism might also contribute to differences between short and long sleepers in social achievements. Stage 3 sleep might be essential for humans. The short sleep latency (≤8 min) of short sleepers in multiple sleep latency tests should be interpreted cautiously, since it was of the same severity as required for a diagnosis of narcolepsy or idiopathic hypersomnia.